Unveiling invisibility: the lived experiences of former students at New Zealand's second chance education secondary school - Rajesh Ram; Cristopher Lynch (Kōtuitui)
This paper examines the lived experiences of former students who attended a second chance education [SCE] secondary school in New Zealand. Like charter schools in New Zealand, School A (Pseudonym) was established to work in collaboration with a local tertiary education provider and secondary schools within the wider South Auckland region. This collaboration was to provide opportunities for secondary school students who had dropped out or did not fit into the mainstream education system in New Zealand. Drawing on qualitative methods, we give meaning to the lived experiences of eight individuals and highlight how sociocultural and socioeconomic factors led these individuals to feel invisible in the mainstream education system and how School A's practices, such as addressing teachers by their first names and emphasising hands-on learning experiences transformed lives. This research provides insights into the potential of SCE schools in reengaging disengaged youth and fostering a pathway towards creating a responsible citizen.